2013
DOI: 10.1007/s00125-013-3037-3
|View full text |Cite
|
Sign up to set email alerts
|

Oligopeptides stimulate glucagon-like peptide-1 secretion in mice through proton-coupled uptake and the calcium-sensing receptor

Abstract: Aims/hypothesisIngested protein is a well-recognised stimulus for glucagon-like peptide-1 (GLP-1) release from intestinal L cells. This study aimed to characterise the molecular mechanisms employed by L cells to detect oligopeptides.MethodsGLP-1 secretion from murine primary colonic cultures and Ca2+ dynamics in L cells were monitored in response to peptones and dipeptides. L cells were identified and purified based on their cell-specific expression of the fluorescent protein Venus, using GLU-Venus transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
167
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(189 citation statements)
references
References 33 publications
3
167
1
1
Order By: Relevance
“…This increase in the density of GLP-1-producing cells in the common limb could be linked to an increased flow of nutrients and bile, since both bile [7], fatty acids, carbohydrates [8] and oligopeptides [9] are known secretagogues of GLP-1 and, thus, are potential stimulators of GCG expression. Similarly, our findings are consistent with the increased postprandial plasma levels of GLP-1 found after RYGB [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in the density of GLP-1-producing cells in the common limb could be linked to an increased flow of nutrients and bile, since both bile [7], fatty acids, carbohydrates [8] and oligopeptides [9] are known secretagogues of GLP-1 and, thus, are potential stimulators of GCG expression. Similarly, our findings are consistent with the increased postprandial plasma levels of GLP-1 found after RYGB [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms behind the sensing of and the secretory effects of peptone/amino acids have not been investigated in any detail.Possible mechanisms involve apical amino-acid/sodium cotransport into the cells, with subsequent depolarization and calcium-dependent secretion although metabolism of amino acids may also play a role. Recent single cell studies have suggested that protein-sensing could be linked to the Calcium-sensing receptor (CasR) and the peptide transporter-1 (PEPT1) 11 . However, this might be in addition to the other mechanisms.…”
Section: Proteinmentioning
confidence: 99%
“…In primary mouse colonic cells, peptone, a meat hydrolysate provided a good stimulus for the incretin hormones 11,63 . Also a number of amino acids have been shown to affect GLP-1 secretion in in vitro studies, including glutamine, alanine, arginine, phenylalanine, asparagine 10,20,43,55,67 .For glutamine, as a consequence, this has been taken into clinical studies as well.In the isolated perfused rat small intestine, peptone was a powerful stimulus of GLP-1 secretion, thusthe effect inculturedcells translated to the cells in situ.…”
Section: Proteinmentioning
confidence: 99%
“…The sensing of these larger protein digestion products has been linked to the activation of MAPKs (52, 53) and the activity of the brush border H + -coupled transporter of dipeptides and tripeptides, peptide transporter 1 (PEPT1) (54,55). Both PEPT1-and CaSR-dependent pathways were recently implicated in the sensing of peptones and dipeptides and tripeptides by primary L cells (56). Another receptor, lysoon plasma incretin levels (33), although small GLP1 responses triggered by oral fructose might be attributable to metabolism (37), as apical fructose uptake is mediated by a non-electrogenic transporter GLUT5.…”
Section: Molecular Mechanisms Underlying Gut Chemosensingmentioning
confidence: 99%
“…In recent years gut microbiota have been increasingly recognized as a fundamental component of host metabolism, and shifts in bacterial populations have been associated with endocrine disorders such as obesity and type 2 diabetes (98-101). Gut microbiota phosphatidic acid receptor 5 (LPAR5, also known as GPR92/93), was reported to mediate peptone-stimulated CCK release in Lpar5-overexpressing STC-1 cells (57), although its expression is not enriched in native I cells (49) or L cells (56). As GLP1 secretion was found not to be impaired in primary colonic cultures from Lpar5 knockout mice (56), further work is required to elucidate what role, if any, LPAR5 plays in intestinal chemosensing.…”
Section: Gut Microbiota Host Defense and Eec Signalingmentioning
confidence: 99%